PENERAPAN MODEL PEMBELAJARAN PBL TERHADAP HASIL BELAJAR SISWA PADA MATERI GETARAN KELAS VIII DI SMP NEGERI 6 WATUBANGGA - Ni Wayan Sukma Wulandari; Sutrisnawati Mehora (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to analyze the influence of problem-based learning (PBL) on student learning outcomes in vibration material in class VIII SMP Negeri 6 Watubangga. The method used in this research is a descriptive research method with a quantitative approach. The sample in this research was 17 students in class VIII of SMP Negeri 6 Watubangga. The instrument used in this research is a learning outcomes test for students during the learning process. Based on the results of the analysis of the increase in learning outcomes which refers to the initial test and final test data for all 17 students, it was found that the lowest increase in results was 0.4 and the highest was 1 with an average value of Normalized gain 〈g〉 of 0.75 which was in the high category. The research conclusion shows that the initial cognitive abilities of some students fail with the lowest achievement score of 20. After implementing the PBL learning model, it shows that PBL learning is effective in increasing students' understanding of the concept of vibration. Therefore, PBL is recommended as an innovative learning model that can be applied in science learning at the junior high school level.